Strategies for sustainable upgrading in global value chains: The Ivorian and Ghanaian mango sectors - Jan Grumiller; Christoph Arndt; Hannes Grohs; Werner Raza; Cornelia Staritz; Bernhard Tröster (Austrian Foundation for Development Research (ÖFSE), 2018)
This policy note presents policy recommendations for a sustainable development strategy targeting the Ivorian and Ghanaian mango sectors. Based on a GVC and SWOT analysis, we conclude that the mango sectors in both countries yield significant potential for promoting socially inclusive and environmentally sustainable production and employment. To this end, in both countries, a stronger focus on industrial policies targeting the key challenges in the respective mango sector is however needed.
Keywords: 330